Pests and partners: synanthropic insect roles in reindeer herding of North Asia and their implications for multispecies archaeologies - Morgan Windle; Morgan Windle; Stephan Dudeck; Stephan Dudeck; Tanja Schreiber; Tanja Schreiber; Hans Whitefield; Henny Piezonka (Pastoralism)
Across Northern Eurasia, reindeer have long shaped the socio-cultural fabric of hunter-fisher societies. Today, descendant communities continue multispecies lifeways, forming symbiotic relationships within boreal ecosystems. Reindeer, regarded as animate persons, exist as both herded and wild partners. While the dynamics of these communities have been widely studied, the smallest actors in this system—namely insects—have remained largely overlooked, particularly in discussions of reindeer domestication and archaeology. Expanding ontological perspectives and engaging with new narrative approaches open avenues for recognizing other animate beings as co-constructors of social, economic, and cultural systems. Traditional hunter-herding practices in the West Siberian and Northwest Mongolian taigas offer insights into early human-reindeer cooperation, domestication, and their archaeological traces. This study employs a collaborative, multidisciplinary approach to examine how synanthropic insects—such as mosquitoes, midges, and horseflies—shape hunter-herder lifeways, despite their absence from the archaeological record. Fieldwork with Sel’kup, Khanty, and Tsaatan communities highlights the critical role of insects in herding and mobility patterns, influencing niche construction strategies. These case studies reveal new multispecies parameters that will enhance interpretations of the archaeological record.